2016
DOI: 10.1021/acs.orglett.6b00450
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Benzylic Arylation of Pyridylmethyl Silyl Ethers: One-Pot Synthesis of Aryl(pyridyl)methanols

Abstract: An efficient palladium-catalyzed direct arylation of pyridylmethyl silyl ethers with aryl bromides is described. A Pd(OAc)2/NIXANTPHOS-based catalyst provides aryl(pyridyl)-methyl alcohol derivatives in good to excellent yields (33 examples, 57–100% yield). This protocol is compatible with different silyl ether protecting groups, affording either the protected or the free alcohols in an effective one-pot process. The scalability of the reaction is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…A further investigation of the eight papers which report these substrates illustrates just how unusual it is for a catalytic reaction to be specific for these positions. 16,47,49,88,103,130,134,135,140 One strategy to activate these positions is demonstrated by four publications from the Walsh laboratory (ref. 16, 103, 134 and 135), and describe the production of di-and tri-arylmethane products through palladium or nickel catalysis.…”
Section: Structure-level Analysis: Reaction Distribution By Structurementioning
confidence: 99%
“…A further investigation of the eight papers which report these substrates illustrates just how unusual it is for a catalytic reaction to be specific for these positions. 16,47,49,88,103,130,134,135,140 One strategy to activate these positions is demonstrated by four publications from the Walsh laboratory (ref. 16, 103, 134 and 135), and describe the production of di-and tri-arylmethane products through palladium or nickel catalysis.…”
Section: Structure-level Analysis: Reaction Distribution By Structurementioning
confidence: 99%
“…These observations prompted us to consider a general strategy for chlorination of alkyl-substituted heteroarenes through in situ formation of alkylidene dihydropyridine intermediates (Figure B, gray box). Resonance activation of heterobenzylic C–H bonds has been promoted in other transformations using Lewis acids; electrophiles, such as alkyl chloroformates and sulfonyl chlorides; additional electron-withdrawing substituents; and transition-metal catalysis. , Here, we develop a complement of methods to achieve site-selective polar chlorination of 2- and 4-alkylpyridines and related heterocycles, setting the stage for tandem C–H chlorination/cross-coupling with amines, azoles, and other important nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a cross‐coupling between α‐alkoxybenzyl anions and aryl halides has emerged as an alternative synthetic approach to 1,1‐diarylmethanols. Walsh and co‐workers demonstrated that a strong base deprotonated the benzylic C−H of benzyl silyl ethers to generate the corresponding α‐alkoxylbenzyl anions, which could be catalytically exploited in palladium‐catalyzed cross‐coupling with aryl halides (Scheme 1A) [4] . Although this method avoids the use of highly basic organometallic reagents, a rare metal, palladium catalyst was essential for the bond forming process.…”
Section: Introductionmentioning
confidence: 99%